2009
DOI: 10.1002/bit.22533
|View full text |Cite|
|
Sign up to set email alerts
|

Post‐translational events of a model reporter protein proceed with higher fidelity and accuracy upon mild hypothermic culturing of Chinese hamster ovary cells

Abstract: Chinese hamster ovary cells (CHO) are routinely used in industry to produce recombinant therapeutic proteins and a number of studies have reported increased recombinant mRNA levels at temperatures <37 degrees C. Surprisingly, the effect of reduced temperature on mRNA translation in CHO cells has not been investigated despite this process being highly responsive to environmental stresses. The relationship between low temperature culturing of CHO cells and mRNA translation was therefore investigated using labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…To explain why the opposite effect is often observed, reports suggest increased RNA half-life, increased transcription of certain target genes through specific binding sites within their promoter regions, alternative mRNA splicing, and CSP-mediated Internal Ribosome Entry Segments (IRESs) in certain mRNAs may be responsible for increased gene expression at sub-physiological temperatures [6]. Recently the Smales' group showed that cap-dependent mRNA translation is not severely attenuated in CHOK1 cells when the culture temperature is shifted from 37 °C to 32 °C [7]. They suggested the increase in protein expression was due to a combination of increased mRNA half-life and improved fidelity of protein folding and post-translational events at 32 °C.…”
Section: Introductionmentioning
confidence: 95%
“…To explain why the opposite effect is often observed, reports suggest increased RNA half-life, increased transcription of certain target genes through specific binding sites within their promoter regions, alternative mRNA splicing, and CSP-mediated Internal Ribosome Entry Segments (IRESs) in certain mRNAs may be responsible for increased gene expression at sub-physiological temperatures [6]. Recently the Smales' group showed that cap-dependent mRNA translation is not severely attenuated in CHOK1 cells when the culture temperature is shifted from 37 °C to 32 °C [7]. They suggested the increase in protein expression was due to a combination of increased mRNA half-life and improved fidelity of protein folding and post-translational events at 32 °C.…”
Section: Introductionmentioning
confidence: 95%
“…Mammalian cells synthesizing large amounts of secreted recombinant protein encounter a number of stresses including ER stress as the secretory pathway becomes overloaded, in addition to nutrient and energy depletion in the later stages of culture, all conditions that increase eIF2α phosphorylation [30]. Additionally, it is often advantageous during the production of recombinant proteins from mammalian cells to switch cells in the later culture stages to mildly hypothermic conditions [29,[31][32][33] since these delay apoptosis, reduce nutrient and energy requirements [34] and, in some cases, enhance the yield of correctly folded protein product [29]. However, hypothermia is in itself perceived as a stress and leads to cell-cycle arrest [35], changes in protein synthesis [36][37][38], differential transcript expression [39,40] and eIF2α phosphorylation [29].…”
Section: Introductionmentioning
confidence: 99%
“…The control of protein synthesis and subsequent polypeptide/protein folding in the ER is directly relevant to recombinant protein production from mammalian cell-expression systems [27][28][29]. Mammalian cells synthesizing large amounts of secreted recombinant protein encounter a number of stresses including ER stress as the secretory pathway becomes overloaded, in addition to nutrient and energy depletion in the later stages of culture, all conditions that increase eIF2α phosphorylation [30].…”
Section: Introductionmentioning
confidence: 99%
“…The reason why the decrease in the culture temperatures increases the specific productivity of a wide range of recombinant proteins still has not been clearly determined yet (Becerra et al 2012). Among the possible causes that could be involved in this phenomenon, it could be mentioned the following: cell cycle arrest in G1 phase, considered as the most metabolically active (Yoon et al 2003a, Yoon et al 2003bBi et al 2004;Trummer et al 2006b), increase in the levels of transcript of the protein and an increase in the stability of the mRNA of the recombinant protein (Yoon et al 2003a;Fox et al 2004;Al-Fageeh et al 2006), increase in the capacity of folding by chaperone proteins of the endoplasmic reticulum (Baik et al 2006;Masterton et al 2009), among others.…”
Section: Introductionmentioning
confidence: 98%